Introducing the Anthology for Computers and the Humanities - Arnold, Taylor; Antoniak, Maria; Escobar, Varela Miguel; Puren, Marie; Oiva, Mila; Regan, Amanda; Tilton, Lauren; Walsh, Melanie (The Association for Computers and the Humanities, 2026)
We present the Anthology of Computers and the Humanities, a new publication designed to host open-access, peer-reviewed proceedings from digital humanities (broadly defined) conferences and workshops. The Anthology provides a home for conference proceedings, offering essential structures such as DOIs and searchability, while being explicitly attuned to the needs of research situated in humanities disciplines.